Contribution to the study on polar constituents from the buds of Rhodomyrtus tomentosa (Ait.) Hassk. (Myrtaceae) - Giang, Phan Minh; Ha, Tran Thi; Hong Anh, Nguyen Thi; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
A flavonol glycoside, kaempferol 3-O-β-sambubioside (1) was isolated in a study on the polar constituents of the buds of Rhodomyrtus tomentosa Ait. Hassk. (Myrtaceae). Its structure was determined by spectroscopic methods. Keywords: Rhodomyrtus tomentosa; Myrtaceae; flavonol glycoside.